2021
DOI: 10.1016/j.redox.2020.101764
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of survival odds in COVID-19 by zinc, age and selenoprotein P as composite biomarker

Abstract: SARS-CoV-2 infections cause the current coronavirus disease (COVID-19) pandemic and challenge the immune system with ongoing inflammation. Several redox-relevant micronutrients are known to contribute to an adequate immune response, including the essential trace elements zinc (Zn) and selenium (Se). In this study, we tested the hypothesis that COVID-19 patients are characterised by Zn deficiency and that Zn status provides prognostic information. Serum Zn was determined in serum samples (n = 171) collected con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
166
4
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(189 citation statements)
references
References 84 publications
6
166
4
5
Order By: Relevance
“…SELENOP concentrations were also significantly lower than the reference group, and mean SELENOP concentrations in LT samples (1.9 ± 0.7 mg/L) were even below the 1st percentile of the EPIC cohort (2.3 mg/L) ( Figure 3 B). The vast majority of samples displayed a profound deficit in either Se or SELENOP (93.7%), and most of these samples displayed a combined deficit (81.6%) with respect to the thresholds for Se deficiency at 70 µg/L and SELENOP at 2.56 mg/L [ 43 ] ( Figure 3 C).…”
Section: Resultsmentioning
confidence: 99%
“…SELENOP concentrations were also significantly lower than the reference group, and mean SELENOP concentrations in LT samples (1.9 ± 0.7 mg/L) were even below the 1st percentile of the EPIC cohort (2.3 mg/L) ( Figure 3 B). The vast majority of samples displayed a profound deficit in either Se or SELENOP (93.7%), and most of these samples displayed a combined deficit (81.6%) with respect to the thresholds for Se deficiency at 70 µg/L and SELENOP at 2.56 mg/L [ 43 ] ( Figure 3 C).…”
Section: Resultsmentioning
confidence: 99%
“…This pattern was evident on viral infections through several modulation pathways such as fusion, replication, viral protein translation, viral particle entry, especially those involving respiratory system pathology. 105,118,121,123,124 A possible clarification for the relevance of zinc in the treatment of COVID-19 conditions has been attributed to its immunomodulatory effect, antiviral property, as well as its ability to regulate the inflammatory response. 112,125,126 The possible mechanisms by which zinc might be effective in the therapy of COVID-19 are based on the previous evidence with other common viral infections and limited experience with COVID-19 [ Figure 2].…”
Section: Anti-viral Effects Of Zinc As a Therapy For Covid-19mentioning
confidence: 99%
“…In a similar line of study, serum zinc level was found to be relatively low in samples collected from COVID-19 patients compared to the healthy counterparts. The average serum zinc level was remarkably low in the samples collected from the non-surviving COVID-19 patients (n=6) as compared to the surviving COVID-19 patients (n=29) [94] . In another uncontrolled case series study with COVID-19 patients, a high dose of oral zinc salt resulted in clinical recovery, improved oxygenation, and less shortness of breath among those patients [95] .…”
Section: Zinc: Effects On Covid-19 Patientsmentioning
confidence: 85%